Abrasion resistance and toughness of a ductile iron produced by two molding processes with a short austempering - Dueñas, J.R (2019)
Austempered ductile irons (ADI) have been extensively used in applications that require a high wear resistance. To further improve it, this work analyzes the effects of both two molding conditions and a short austempering process in the abrasion resistance and toughness of a ductile iron. To do so, the cast and heat-treated specimens were analyzed using several stages including microstructural analysis, mechanical testing and roughness measurements. The experimental results showed that both molding conditions induced the precipitation of massive carbides during solidification, yet the green sand samples had the highest amount. Furthermore, the short austempering produced a microstructure composed by refined ausferrite, with a surrounding mixture of untempered martensite and unreacted austenite. In addition, the ADI presented the best wear resistance due to its hard microstructure which further strengthened during the tests. Finally, the toughness of the ADI was impaired primarily by the mixture of untempered martensite and unreacted austenite.